Tuning Cholesteric Selective Reflection In Situ Upon Two‐Photon Polymerization Enables Structural Multicolor 4D Microfabrication. Issue 2 (14th November 2021) - Ritacco, Tiziana; Aceti, Dante M.; De Domenico, Gianfranco; Giocondo, Michele; Mazzulla, Alfredo; Cipparrone, Gabriella; Pagliusi, Pasquale
Abstract: Effective optical elements with tailored properties often rely on the capability to tune the material's structure at the nanoscale. Thanks to their self‐organized 1D helical arrangement, cholesteric liquid crystals represent a beautiful example of optical materials whose properties are governed by their supramolecular structure. According to the Bragg's law, selective reflection of circular polarized light occurs for wavelengths within the photonic band gap, which, beside the refractive indices, depends on the helix pitch. Here, polymeric microstructures with tailored PBG are demonstrated by two‐photon polymerization direct laser writing in cholesteric reactive mesogens. Turning a renowned disadvantage into an opportunity, the shrinkage upon the layer‐by‐layer photopolymerization is exploited to control the effective helix pitch. Starting from a PBG of the precursor in the near infra‐red, micro‐cylinders which exhibit Bragg selective reflection at lower wavelength ranges, down to the opposite end of the visible spectrum, are fabricated in a single‐step process by tuning the laser exposure parameters. As a proof‐of‐concept, a 4D quick response (QR) micro‐tag, which adds the polarization‐selective structural color and the height of the blocks to the usual 2D black/white QR codes, is demonstrated as a novel paradigm of optical anti‐counterfeiting microdevice. Abstract : Full‐color, single‐step, microfabrication is demonstrated by two‐photon direct laser writing in cholesteric liquid crystalline photoresists. The highly localized photoexcitation allows to regulate the chiral photonic band gap over the whole visible range, with microscale spatial resolution, thus adding a fourth dimension to the 3D additive manufacturing technique. A 4D quick response (QR) tag is reported as proof‐of‐concept.